Comparison of Two Different Anesthesia Methods in Patients Undergoing Percutaneous Nephrolithotomy - Solakhan, Mehmet; Bulut, Ersan; Erturhan, Mehmet Sakip (Urology Journal, 2019)
Purpose: The study aims to compare the effectiveness, safety and costs of two different anesthesia methods in percutaneous nephrolithotomy (PCNL) operations. Material and Method: In our study, data was retrospectively examined of 1657 patients who underwent PCNL due to renal calculi between 2009 and 2017. Patients were separated into two groups according to the type of anesthesia; as those who underwent PCNL by general anesthesia (GA) (n = 572) and those under spinal anesthesia(SA) (n = 1085). Standard PCNL technique was used in both groups. Gender, age, operation duration, period of hospitalization, stone-free ratio, post-operative narcotic analgesic need and complications were compared between these two groups. Results: A total of 1657 patients consisting of 1064 (64.2%) male patients and 593 (35.8%) female patients were included in the study. The average age of the all patients was 33.2 ± 12.4 (range 16-74) years. The two groups were similar in terms of mean age, gender, stone size, stone location and body mass index. Mean operation time was significantly shorter in the SA group than in the GA group (81.8 ± 33.9 minute vs. 118.2 ± -42.9 minute respectively, P < .001). Mean period of hospitalization was remarkable shorter in the SA group than in the GA group (30.0 ± 9.9 hours vs. 38.4 ± 11.2 hours respectively, P < .001). Post-operative narcotic analgesic need rate was significantly higher in the GA group than in the SA group (33.4% vs. 10.9%, respectively, P < .001). Anesthesia cost was found significantly lower in the SA group than in the GA group (USD 21.3±2.8 vs. USD 83.6 ± 9.5, respectively, P < .001). Significant difference was not observed between both groups in terms of stone-free ratio, amount of bleeding, fluoroscopy time, pre-operative and post-operative complications. Conclusion: Compared to those performed with GA, PCNL performed with SA is a safe, effective and low-cost method.